Universities and Climate Change Introducing Climate Change to University Programmes - Leal Filho, Walter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Climate change is a matter of global concern and specific sectors of society such as universities need to engage and be active in the search for regional and local solutions for what is a global problem. Despite the fact that many universities all around the world are undertaking remarkable efforts in tackling the challenges posed by climate change, few of such works are widely documented and disseminated. The book "Universities and Climate Change" addresses this gap. The book pursues three aims. Firstly, it presents a review of the approaches and methods to inform, communicate and educate university students and the public on climate change being used by universities around the world. Secondly, it introduces initiatives, projects and communication strategies undertaken by universities with a view to informing students and other stakeholders in order to raise awareness on matters related to climate change. Finally, the book documents, promotes and disseminates some of the on-going initiatives.
Climate Change at Universities: Results of a World Survey -- Path to the Future for Climate Change Education: A University Project Approach -- Australian Universities, Government Research and the Application of Climate Change Knowledge in Australian Coastal Zone Management -- The Impact of Universities on the Climate Change Process -- University of Minnesota Water-Based Nitrogen Budget -- Sustainable Literacy and Climate Change: Engagement, Partnerships, Projects -- Getting to the Heart of Climate Change Through Stories -- Climate Change Education in the Curricula of Technical and Classical Universities -- Interdisciplinary and Interfaculty Approaches in Higher Education Capable of Permeating the Complexity of Climate Change -- The Campus as a Classroom: Integrating People, Place, and Performance for Communicating Climate Change -- How to Educate for a Healthy Climate at a University? An Intergenerational Cooperation (A Case Study from Slovakia) -- Targeting a Low-Carbon University: A Greenhouse Gas Reduction Target for the Australian Technology Network of Universities -- Malaysian University Students$1 (BAwareness of Geographic Information Systems -- Lifestyle Changes: Significant Contribution to GHG Emission Reduction Efforts -- Universities as Learning Organizations for Sustainability? The Task of Climate Protection -- Using a Spare Time University for Climate Change Education -- Embracing the Future: The Ball State University Geothermal Project -- Engaged Learning for Climate Change: The Perils and Potentials of Collaborative Partnerships and Projects -- Learning for Climate Responsibility: Via Consciousness to Action -- CO2 Emissions Impact of Sustainable Food Procurement: Informing University Policy -- Graduate Studies of Global Change at the University of Latvia.s
Keywords: Economics; Climatic changes; Environmental management; Environmental economics; Economics/Management Science; Environmental Economics; Climate Change; Environmental Management